2007
DOI: 10.1080/10731190600974376
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aspects of the High Oxygen Afinity of Non-Hypertensive Hexa Pegylated Hemoglobin, [(SP-PEG5K)6-Hb]

Abstract: The development of hexaPEGylated Hb, (SP-PEG5K)(6)-Hb, using the newly designed thiolation-mediated maleimide chemistry based PEGylation, has validated the concept that engineering 'plasma volume expander' -like properties to Hb neutralizes its vasoactivity. The high O(2) affinity of hexaPEGylated Hb has been attributed to the two PEG-5K chains on its two Cys-93(beta) residues. In an attempt to map the influence of the additional four PEG-5K chains of HexaPEGylated Hb on the O(2) affinity, we have now investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…This observation is consistent with the observation that EAF P5K6 rHb generated using the rHb is also an high oxygen affinity species (Li et al 2007) reflecting the high oxygen affinity inducing activity of EAF PEGylation targeted to exclusively to the e-amino groups. At Einstein, Hb has also been EAF PEGylated exclusively at e-amino groups under oxy conditions achieved through the reversible protection of Cys-93(b) during EAF PEGylation and this product is also high oxygen affinity species.…”
Section: Hemospan and Euro-peg Hbsupporting
confidence: 83%
See 1 more Smart Citation
“…This observation is consistent with the observation that EAF P5K6 rHb generated using the rHb is also an high oxygen affinity species (Li et al 2007) reflecting the high oxygen affinity inducing activity of EAF PEGylation targeted to exclusively to the e-amino groups. At Einstein, Hb has also been EAF PEGylated exclusively at e-amino groups under oxy conditions achieved through the reversible protection of Cys-93(b) during EAF PEGylation and this product is also high oxygen affinity species.…”
Section: Hemospan and Euro-peg Hbsupporting
confidence: 83%
“…All three PEGylated derivatives are high oxygen affinity molecular species since all have the Cys-93(b) PEGylated and attenuate the in vivo hypertensive activity of the acellular Hb to a considerable degree (Li et al 2006(Li et al , 2007. The oxygen affinities of these PEGylated species are comparable.…”
Section: Hemospan and Euro-peg Hbmentioning
confidence: 84%
“…It was shown in a recent study that the conjugation of PEG-chains to lysine residues of Hb by the thiolation-mediated PEGylation induced structural changes by increasing the hydration shell, which further helped in the stabilization of favorable relaxed state conformation of Hb. 33 This stabilization of relaxed state by PEG's hydration shell or modifications that help the transition of Hb from T to R conformation may be responsible for the lowering of p50. 13 However, in the current method of conjugation, it is not feasible to know about which amino group perturbation is critical for lowering the p50 of Hb molecules and thus the lowering of the p50 of the final conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown in a recent study that the conjugation of PEG-chains to lysine residues of Hb by the thiolation mediated PEGylation induced structural changes by increasing the hydration shell, which further helped in the stabilization of relaxed high affinity conformation [44]. It was shown that methemoglobin levels needs to be maintained below 10% in PEG-conjugated hemoglobins to efficiently oxygenate tissues [45].…”
Section: Discussionmentioning
confidence: 99%